An Analysis Factors Affecting the Cases of Pneumonia in Toddlers at Public Health Center (Puskesmas) Pati I - Yuliniar, Ulvarine; Wijayanti, Yuni; Indriyanti, Dyah Rini (Universitas Negeri Semarang, 2021)
Pneumonia is an inflammatory condition of the lung primarily affecting the small air sacs known as alveoli. It is an Acute Respiratory Infection (ARI) that attacks the lung tissue which is characterized by coughing accompanied by rapid breathing or shortness of breath. Pneumonia often occurs and attacks the community, especially toddlers at Public Health Center (PUSKESMAS) Pati I in Pati Regency. There are many unknown factors of this disease. The purpose of this study was to analyze the intrinsic and extrinsic factors causing pneumonia in children under five years old at Publich Health Center (PUSKESMAS) Pati I. The research method used in this study was an analytical survey with a case control study design. The total sampling used was 35 toddlers. The sampling technique used was total sampling. Observations were made through direct observation and measurement of age, breastfeeding, nutritional status, family income, family smoking habits, ventilation, and the incidence of pneumonia in children under five years old or toddlers. The data in this study was analyzed by using Univariate, Bivariate and Multivariate analysis. The results showed that nutritional status (p=0.046), smoking habits (p=0.03) and ventilation (p=0.000) has an effect on the incidence of pneumonia. Meanwhile, age (p=0.398), breastfeeding (p=0.464), and family income (p=0.497) has no effect on the incidence of pneumonia. The most influential factor on the incidence of pneumonia in children under five years old or toddlers is home ventilation with an odds ratio of 40,866. Efforts to improve the health condition of toddlers with pneumonia at Public Health Center Pati I are carried out with Psychoeducation and Health Education activities.